Bread wheat TaSPO11‐1 exhibits evolutionarily conserved function in meiotic recombination across distant plant species. (10th July 2020) - Da Ines, Olivier; Michard, Robin; Fayos, Ian; Bastianelli, Giacomo; Nicolas, Alain; Guiderdoni, Emmanuel; White, Charles; Sourdille, Pierre
SUMMARY: The manipulation of meiotic recombination in crops is essential to develop new plant varieties rapidly, helping to produce more cultivars in a sustainable manner. One option is to control the formation and repair of the meiosis‐specific DNA double‐strand breaks (DSBs) that initiate recombination between the homologous chromosomes and ultimately lead to crossovers. These DSBs are introduced by the evolutionarily conserved topoisomerase‐like protein SPO11 and associated proteins. Here, we characterized the homoeologous copies of the SPO11‐1 protein in hexaploid bread wheat ( Triticum aestivum ). The genome contains three SPO11‐1 gene copies that exhibit 93–95% identity at the nucleotide level, and clearly the A and D copies originated from the diploid ancestors Triticum urartu and Aegilops tauschii, respectively. Furthermore, phylogenetic analysis of 105 plant genomes revealed a clear partitioning between monocots and dicots, with the seven main motifs being almost fully conserved, even between clades. The functional similarity of the proteins among monocots was confirmed through complementation analysis of the Oryza sativa (rice) spo11‐1 mutant by the wheat TaSPO11‐1‐5D coding sequence. Also, remarkably, although the wheat and Arabidopsis SPO11‐1 proteins share only 55% identity and the partner proteins also differ, the TaSPO11‐1‐5D cDNA significantly restored the fertility of the Arabidopsis spo11‐1 mutant, indicating a robust functional conservation of the SPO11‐1 protein activity across distant plants. These successful heterologous complementation assays, using both Arabidopsis and rice hosts, are good surrogates to validate the functionality of candidate genes and cDNA, as well as variant constructs, when the transformation and mutant production in wheat is much longer and more tedious. Significance Statement: We analyzed the three homoeologous copies of the SPO11‐1 gene found in the bread wheat genome. They are very similar but not identical, revealing their parental origin from diploid wheats. These SPO11‐1 proteins contain seven essential and evolutionarily conserved motifs, now found in 105 plant species. The coding sequence of the wheat D copy significantly complemented the rice and Arabidopsis spo11‐1 mutants, indicating strong functional conservation between highly divergent species.